Teks Autentik dalam Pemahaman Membaca Kelas Daring: Efektivitasnya Terhadap Hasil Belajar Pembelajar Muda - Kamila, Fatima; Duwi Purwandari, Junita (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
In understanding foreign language texts, there are several challenges faced by young learners. The transformation of the learning system into online increasingly adds new problems for them. Students' motivation in online learning is relatively low, while the acquisition of foreign language reading comprehension demands great motivation (Fareh, 2010). Authentic text can be a solution to this problem. Therefore, this study was conducted to test its effectiveness in improving young students' reading comprehension in online classes and to examine their perceptions of teaching reading comprehension using authentic texts in online classes. This research is a quasi-experimental research with one group pre-test post-test design. The data generated is quantitative data in the form of student learning outcomes and reading interest questionnaires. The results showed that the use of authentic texts was proven to be effective in resolving new conflicts that arose in the online foreign language reading comprehension class. In addition, students' perceptions of the use of authentic texts are also good. However, the role of teachers and students is needed in its implementation